Corpse-Women. The Representation of Female Bodies between Macabre Beauty and Disgust in Camillo Boito and Igino Ugo Tarchetti (Itinera, 2024)
In the late 19th century, the Scapigliati expressed their reaction to the dominant positivist ideology, which governed the interpretation of reality in the contemporary literature, through the fantastic, the macabre, and the horrific. Science, however, was not excluded from their works; rather, it infiltrated the text, transforming the writer into a sort of anat- omist and the female subjects – described in life or in death – of his narratives into dis- sectible anatomical models, like Venere Medicea by Clemente Susini. Constantly envel- oped in a deathly atmosphere that alters their characteristics, these female bodies evoke impressions in the observing men that oscillate between macabre beauty and disgust, eventually becoming corpses that obsessively haunt the male protagonists’ psyches, also imbuing the settings of the stories with a «maestosa orribilità», as Tarchetti states. Starting from this significant presence in Scapigliatura literature, this article intends to focus particularly on some interesting case studies found in the narratives of Camillo Bo- ito and Igino Ugo Tarchetti. The aim is to explore the forms and functions of this type of representation of the female body within the literary text: “corpse-women”, “skeleton- women”, and “wax-women” wander through the pages of Boito’s Storielle vane (Un corpo and Notte di Natale) and Tarchetti’s works (the novels Fosca and Paolina and the stories Lorenzo Alvati and Bouvard).
Keywords: Scapigliatura, Corpse-Women, Skeleton-Women, Wax-Women, Male Gaze